(untitled) - Tateishi, John; Daniels, Roger (Seattle, 1999)
Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Japanese Americans -- Evacuation and relocation, 1942-1945; Oral history; World War, 1939-1945 -- Personal narratives, American; Người Mỹ gốc Nhật -- Di cư -- 1942-1945